(untitled) (Global Journal of Energy Technology Research Updates, 2020)
Many electricity generating stations are concerned with the reduction of environmental pollution associated with the thermodynamic activities of power plants. Such environmental pollution includes emissions from exhaust gases, cooling tower blowdown, boiler blowdown and demineralization. In this paper, an exergo-environmental analysis was conducted using design data from the Egbin power plant for a 220MW steam power plant. Enhancement was carried out on the plant under varying pressure and temperature conditions to assess the plant’s performance improvements that would lead to more reduction in environmental pollution. The exergy destruction efficiency value indicates that the boiler sub- system gave the highest exergy destruction in the power plant. Also, sustainability indicators such as environmental effect factor, waste exergy ratio and sustainability index factors have been performed and results presented with respect to the plant. The improvement options considered were: (i) increasing the inlet temperature of the high-pressure turbine at constant boiler pressure, and (ii) the second approach, simultaneous increase in inlet temperature of high-pressure turbine and boiler pressure. The result showed that the second improvement approach gave a better improvement approach than the former by reducing the environmental effect factor by 17.32% and increasing the sustainability index factor by 21.54%. These effects ultimately reduced the steam power plant emissions and improved efficient fuel utilization by the plant for sustainable development and for more power production.